Mary B : a novel - Chen, Katherine J., 1990- (Random House, 2018)
What is to be done with Mary Bennet? She possesses neither the beauty of her eldest sister, Jane, nor the high-spirited wit of second-born Lizzy. Even compared to her frivolous younger siblings, Kitty and Lydia, Mary knows she is lacking in the ways that matter for single, not-so-well-to-do women in nineteenth-century England who must secure their futures through the finding of a husband. As her sisters wed, one by one, Mary pictures herself growing old, a spinster with no estate to run or children to mind, dependent on the charity of others. At least she has the silent rebellion and secret pleasures of reading and writing to keep her company. But even her fictional creations are no match for the scandal, tragedy, and romance that eventually visit Mary<U+2019>s own life. In Mary B, readers are transported beyond the center of the ballroom to discover that wallflowers are sometimes the most intriguing guests at the party. Beneath Mary<U+2019>s plain appearance and bookish demeanor simmers an inner life brimming with passion, humor, and imagination<U+2014>and a voice that demands to be heard. Set before, during, and after the events of Pride and Prejudice, Katherine J. Chen<U+2019>s vividly original debut novel pays homage to a beloved classic while envisioning a life that is difficult to achieve in any era: that of a truly independent woman.